Status inconsistency and return to work among foreign-born and native Swedes - Vania Ranjbar; Robin Fornazar; Gunnel Hensing (Epidemiology, Biostatistics and Public Health)
We investigated potential differences in status inconsistency and time to return to work (RTW) from sickness absence between foreign-born and native Swedes, whether inconsistency was associated with RTW, and if this association was stronger for foreign-borns than natives. Significantly fewer native than foreign-born Swedes reported negative status inconsistency, but RTW did not differ between the groups and inconsistency was not associated with RTW. A positive selection of individuals to the Swedish labour market might help explain the findings. This first study of status inconcistency and RTW requires follow-ups in different settings of labour markets and insurance regulations.